Implementation of Kaizen in Various Industries: A Systematic Literature Review - Sihombing, Rustam; Suhaeri; Sarjono; Purba, Humiras Hardi (Performa: Media Ilmiah Teknik Industri, 2000)
Kaizen is a strategic approach that focuses on continuous improvement to increase an organization's efficiency, quality, and productivity. This article explores the implementation of Kaizen in various sectors through a literature review of 45 articles published between 1996 and 2024. This research aims to identify the application, benefits, and challenges of Kaizen in various industries, both manufacturing and services. The results of the review show that Kaizen has been successfully applied in various sectors, especially manufacturing (31 articles), with a focus on methods such as 5S, Kanban, and the PDCA cycle to reduce waste and increase productivity. Additionally, the application of Kaizen has expanded to non-manufacturing sectors, such as healthcare, education, and the public sector, where this approach contributes to operational efficiency and improved services. However, challenges such as resistance to change, limited resources, and lack of management support often become obstacles to implementation. This study provides recommendations for the development of a more strategic and adaptive Kaizen approach in the modern business environment as a relevant and effective management tool in various industrial contexts.